2017
DOI: 10.1038/labinvest.2017.20
|View full text |Cite|
|
Sign up to set email alerts
|

Increased expression of latent TGF-β-binding protein 4 affects the fibrotic process in scleroderma by TGF-β/SMAD signaling

Abstract: Scleroderma is a fibrosis-related disorder characterized by cutaneous and internal organ fibrosis, and excessive collagen deposition in extracellular matrix (ECM) is a major cause of fibrosis. Transforming growth factor-β (TGF-β)/SMAD signaling has a central role in the pathogenesis of fibrosis by inducing abnormal collagen accumulation in ECM, and latent TGF-β-binding protein 4 (LTBP-4) affects the secretion of latent TGF-β to ECM. A previous study indicated that bleomycin (BLM) treatment increased LTBP-4 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
2
23
0
1
Order By: Relevance
“…Furthermore, we observed that expression of these integrin subunits was regulated by TGFβ, as demonstrated by the use of the TGFBR1 (ALK5) kinase inhibitor SB-505124 and exogenously added hTGFβ1. Although TGFβ is widely regarded as an important driver of SSc pathophysiology [1], e.g., because it stimulates the excessive production of collagen type I by skin fibroblasts and enhances the contractile properties of these cells [10], its plasma and serum levels have been a controversial topic for many years; studies have reported increased [11][12][13], equal, and, similarly to our study, decreased levels [14,15] of TGFβ in serum and plasma of the SSc patients. Possibly, these differences can be attributed to the heterogeneity of disease course in SSc or to the heterogeneity of disease duration in our cohort.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, we observed that expression of these integrin subunits was regulated by TGFβ, as demonstrated by the use of the TGFBR1 (ALK5) kinase inhibitor SB-505124 and exogenously added hTGFβ1. Although TGFβ is widely regarded as an important driver of SSc pathophysiology [1], e.g., because it stimulates the excessive production of collagen type I by skin fibroblasts and enhances the contractile properties of these cells [10], its plasma and serum levels have been a controversial topic for many years; studies have reported increased [11][12][13], equal, and, similarly to our study, decreased levels [14,15] of TGFβ in serum and plasma of the SSc patients. Possibly, these differences can be attributed to the heterogeneity of disease course in SSc or to the heterogeneity of disease duration in our cohort.…”
Section: Discussionsupporting
confidence: 84%
“…A possible explanation for the lowered bioactivity of TGFβ we measured in the SSc serum is the increased expression of LTBP4 as was recently identified [13] or the presence of other latency conferring peptides. Alternatively, immune-related compounds present in the serum possibly modulate the abovementioned cellular context of cells in our bioassay and in this way inhibit TGFβ signaling [16].…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the overexpression of TGF-β could induce activation and epithelial-mesenchymal transition (EMT) [ 19 , 20 ], which facilitate fibronectin synthesis, thus, leading to extracellular matrix (ECM) production [ 21 , 22 ]. Furthermore, TGF-β could cause the deposition of ECM and inhibit the degradation of ECM, by stimulating the secretion of growth factors that promote fibrosis, such as mesenchymal marker vimentin, and a-smooth muscle actin (a-SMA) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dermal biopsy specimens from normal controls with no history of autoimmune or other dermal disease were used as control comparators. Dermal samples were transported in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) for processing the same day as described previously [27,28]. The dermal samples were washed in 75% ethanol, phosphate buffered saline (PBS), and DMEM with 10% FBS.…”
Section: Biopsy Specimens and Cell Culturementioning
confidence: 99%
“…A Nikon Eclipse 80i microscope (Nikon, Badhoevedorp, the Netherlands) was used to measure dermal thickness. The maximal distance between the epidermal-dermal junction and the dermal-subcutaneous fat junction in all skin sections described above was analyzed according to the method mentioned in the previous report by Jiaying Lu et al [28]. Two independent examiners performed evaluation of the sections.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%